The Effect Of Zakat, Human Development Index, And Gross Regional Domestic Product On Poverty Rate In Central Lombok Regency - Arifin, Haerul Arifin; Sejati, Kharisma Rindang (IQTISHADUNA, 2024)
Poverty is a common problem faced by developing countries worldwide. Indonesia, as one ofthese countries, countries to strive to solve the issue of poverty for its citizens. One of theprovinces in Indonesia with the highest poverty rate is West Nusa Tenggara Province. Theprovince consists of 2 cities and 8 districts, spanning two islands: Lombok and Sumbawa.Among these districts, Central Lombok Regency stands out with the highest poverty rate.Poverty has become an urgent issue that demands immediate attention. Therefore, a method orinstrument is needed to address the problem of poverty in Central Lombok Regency. The typeand research approach used in this study is a quantitative approach utilizing secondary data. Thedata employed in this research are secondary data sourced from the National Amil ZakatAgency (BAZNAS) of Central Lombok Regency and the Central Lombok Statistics Agency(BPS). The results of this study indicate that zakat has no significant effect on poverty, with at-value of -1.276901 and a probability value of 0.211, which is greater than 0.05. HDI has apositive and significant effect on poverty, with a t-value of 5.143890 and probability value of0.0001, which is smaller than 0.05, while GDRP has a negative and significant effect on poverty,with a t-value of -9.360041 and a probability value of 0.0000, also smaller than 0.05.furthermore, the results of the simultaneous that (F-test) show that zakat, human developmentindex, and gross regional domestic product have a significant combined affect on poverty inCentral Lombok Regency, with a probability F value of 0.000002, which is smaller than 0.05.